INOVASI PRODUK MELALUI STRATEGI IMITASI DALAM MENGHADAPI PERSAINGAN PRODUK IMPOR (IMPLEMENTASI STRATEGI IMITASI PADA STUDI KASUS EDAM BURGER DI DEPOK) - Hasnin, Hannisa Rahmaniar (prodima@fe.uika-bogor.ac.id, 2016)
It is important for medium-sized franchise to compete with another larger franchise in order to survive and develop. This paper describes the study on the process realization of competitiveness, which is derived from imitation to innovation strategy changes. This changes is indicated by the company’s focus on low cost, and marketing products that has focused on the medium consumers segmentation. The results of this research was conduct through in- depth interviews to the franchisees and surveys to the costumers, it was found that the innovation can attract costumers and differentiate Edam Burger from other companies. In addition, by focusing on low cost and specific market segments, making the company have competitiveness againts other competitors.